Aerodynamics‐Based Triboelectric Nanogenerator for Enhancing Multi‐Operating Robustness via Mode Automatic Switching. (10th April 2022) - Liu, Yuan; Yan, Wenjie; Han, Jiajia; Chen, Baodong; Wang, Zhong Lin
Abstract: The multi‐operating robustness of triboelectric nanogenerators (TENGs) is still an awkward issue that must be solved to achieve practicality and industrialization. Here, an aerodynamics‐based TENG (AB‐TENG) is developed by combining it with a propeller and rotor, which can switch automatically between contact and separation mode. The separation speed can be reduced to 150 rpm by optimizing the spring stiffness coefficient, which maintains 95.18% of the electrical output after continuous operation for more than 1.378 million cycles. Combining with power management circuit, these capacitors of 0.56, 1, 3.3, and 10 mF can be charged quickly to 3 V within 7.3, 9.3, 16.7, and 43.4 s, respectively. In addition, AB‐TENG can power 6 digital hygrothermographs in parallel by harvesting irregular airflow or drive one Bluetooth‐enabled, 6 commercial LED bulbs of 3 W or 240 green LED lamp beads in parallel, respectively. This work provides an effective strategy to improve the multi‐operating robustness of TENGs, and more importantly, to overcome the mechanical durability and electrical stability difficulties of the technique at high rotational speed caused by abrasion limit of triboelectric materials, and may reveal its potential in the distributed energy and Internet of Things. Abstract : An aerodynamics‐based triboelectric nanogenerator is developed by combining it with a commercial propeller and rotor that can switch automatically between contact and separation mode, thus achieving ultra‐high mechanical durability and stable electrical output. The separation speed can be reduced to 150 rpm by optimizing the spring constant, which maintains 95.18% of electrical output after continuous operation for more than 1.378 million cycles.